Risk as a specific sign of agreement on implementation of scientific research or experimentally designer and technological works - Великанова, Марина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article is analysed the subject of agreement  on implementation of research or experimentally designer and technological works. An author is done a conclusion that creative character of works, executable after an agreement, influences on legal description of this agreement and generates risks, inherent exactly to this agreement.